2020
DOI: 10.30699/jidai.32.3.4.59
|View full text |Cite
|
Sign up to set email alerts
|

Angular Photogrammetric Analysis of the Soft Tissue Facial Profile and Sexual Dimorphism in Young Adults in Zanjan

Abstract: Background and Aim: Facial features are different depending on gender and race. These features are usually studied in profile view. Angular evaluation of the facial soft tissue profile is important in males and females of different races for correct diagnosis and treatment planning. For this reason, in the present study, we measured the facial profile angles in young adults in Zanjan. Materials and Methods: In this descriptive cross-sectional study, the photographs of 35 males and 35 females between 16 to 30 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…48 Results of similar studies assessing different regions and populations have also been reported. 40,[42][43][44]46,[51][52][53] The soft tissue total convexity (Gl-Prn-Pg) angle mean values obtained from females and males in our study seem to be compatible with the measurement average results of some studies. 40,42,43,52 In contrast, although the results were obtained from the same population, they differ from the results of Malkoç et al 48 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…48 Results of similar studies assessing different regions and populations have also been reported. 40,[42][43][44]46,[51][52][53] The soft tissue total convexity (Gl-Prn-Pg) angle mean values obtained from females and males in our study seem to be compatible with the measurement average results of some studies. 40,42,43,52 In contrast, although the results were obtained from the same population, they differ from the results of Malkoç et al 48 .…”
Section: Discussionsupporting
confidence: 89%
“…Soft tissue total convexity facial angle (Gl-Prn-Pg) measurement studies were carried out in the Anatolian population among different age groups including adolescents50 and adults 48. Results of similar studies assessing different regions and populations have also been reported 40,42–44,46,51–53. The soft tissue total convexity (Gl-Prn-Pg) angle mean values obtained from females and males in our study seem to be compatible with the measurement average results of some studies 40,42,43,52.…”
Section: Discussionsupporting
confidence: 88%